World Trade Organization: The Multilateral Trade Framework for the 21 st Century and U.S. Implementing Legislation - Stewart, Terence P., ed. (Washington, D.C. America Bar Association. Section of International Law and Practice, 1996)
Contiene: Chapter One. The Uruguay Round and the Launch of the WTO: Significance Challenges by John H. Jackson -- Chapter Two. The Uruguay Round Agreements Act: An Overview of Major Issues and Potential Trouble Spots by Terence P. Stewart -- Chapter Three. The Marrakesh Agreement Establishing the World Trade Organization by Amelia Porges -- Chapter Four. Market Access by Mark R. Sandstrom, Julia M. Cheung and Michele D. Lynch -- Chapter Five. Reforming Global Trade in Agriculture by Paul C. Rosenthal and Lynn E. Duffy -- Chapter Six. Sanitary and Phytosanitary Measures by Marsha A. Echols -- Chapter Seven. Uruguay Round Textile and Apparel by Robert C. Cassidy, Jr. and Stuart M. Weiser -- Chapter Eight. Antidumpping by Alan M. Dunn -- Chapter Nine. The Subsidies Agreement by M. Jean Anderson and Gregory Husisian -- Chapter Ten. Dispute Settlement in Antindumping and Countervailing Duty Cases by James R. Cannon, Jr. -- Chapter Eleven. The Agreement on Safeguards: U.S.Law Leads Revitalization of the Escape Clause by Janet A. Nuzum -- Chapter Twelve. Agreement on Trade Related Investment Measures (TRIMS): Limitations and Prospects for the future by DAnie, M. Price and P. Bryan Christy -- Chapter Thirteen. Trade-Related aspects of Intellectual Property by L. Peter Farkas -- Chapter Fourteen. General Agreement on Trade in Service -- Chapter Fifteen. Government Procurement by Alan Kashdan -- Chapter Sixteen. Section 301 and Dispute Settlement in the World Trade Organization by Richard O. Cunningham and Clint N. Smith -- Chapter Seventeen. Special and Differential Treatment for Developing Countries by Alice Alexandra Kipel -- Chapter Eighteen. How the Uruguay Round will change the practice of International Trade Law in the United States: Two Views: One. by Alan Wm. Wolff and John A. Ragosta. Two by Homer E. Moyer
Keywords: ACUERDOS ARANCELARIOS; AGRICULTURA; ARANCELES PREFERENCIALES; COMERCIO DE SERVICIOS; DUMPING; GATT; INVERSIONES; LIBERALIZACION DEL INTERCAMBIO; OMC; PAISES EN DESARROLLO; SANIDAD AGROPECUARIA; SUBSIDIOS; TEXTILES; NEGOCIACIONES COMERCIALES MULTILATERALES